2019
DOI: 10.37358/rc.18.12.6755
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of FeCoWYB-based Ferromagnetic Alloys with a Small Addition of Pt

Abstract: The paper presents the results of research on the effect of Pt addition in the amount of 2 to 3% at. in to bulk Fe61Co10B20Y8-xW1Ptx alloy on its structure and magnetic properties. Alloys in the form of tiles were made by pressing a liquid alloy into a copper liquid-cooled mold. Structural examinations were carried out using X-ray diffraction (XRD). The magnetic properties were examined using a vibration magnetometer (VSM). Based on structural investigations, the occurrence of crystalline phases, i.e.: a-Fe, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The total proportion of crystalline phases with Fe is 34% + 22% + 5% = 61%. The remaining part of the alloy, i.e., 39%, is an amorphous matrix with folding Fe 51 B 28 (rest) 21 . The calculated percentage of atoms in the identified crystalline phases is given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total proportion of crystalline phases with Fe is 34% + 22% + 5% = 61%. The remaining part of the alloy, i.e., 39%, is an amorphous matrix with folding Fe 51 B 28 (rest) 21 . The calculated percentage of atoms in the identified crystalline phases is given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Alloys with added Pt make up an interesting group of materials, with appropriate chemical compositions for enabling the production of nanocrystalline samples. For several years, the authors have been involved in the production, and testing of the ferromagnetic properties, of classical, bulk amorphous, and nanocrystalline alloys [21][22][23][24]. As are sult of numerous literature studies, the authors have found that there are many publications on ferromagnetic materials with added Pt, the samples being produced in the form of thin layers or ribbons [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%